Infancia, calle y supervivencia: el caso de La Paz y El Alto (Bolivia) - Cavagnoud, Robin (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
Children out of family relationships enter the world of street and socialize with groups of peers with whom they share daily activities like work, theft and alcohol and inhalants consumption. Their lives are commonly associated with survival. However, the study of their life courses shows that the use ofthis term is not always adequate. Following implementation of supports and forms of stability that children reach to maintain with peers and associations, survival gives way to a relative control, random but real, of their destiny. From a fieldwork in La Paz and El Alto (Bolivia) with observations and children life stories in street situation, the article highlights transitions to and out of survival in their biographical course to characterize this notion.

Los niños que rompen los vínculos con su familia entran en el universo de la calle y se socializan con grupos de pares, con los cuales comparten actividades cotidianas como el trabajo, el robo o el consumo de alcohol e inhalantes. Sus condiciones de existencia se asocian frecuentemente con la supervivencia. Sin embargo, el estudio de sus trayectos de vida enseña que el uso de este término no resulta siempre adecuado. Según la implementación de soportes y las formas de estabilidad que los niños logran mantener con sus pares y el medio asociativo, la supervivencia desaparece en favor de un control, aleatorio pero real, de su destino. A partir de una investigación en La Paz y El Alto (Bolivia) compuesta por observaciones y relatos de vida de niños y jóvenes en situación de calle, este artículo evidencia las transiciones hacia y fuera de la supervivencia en su itinerario biográfico con el fin de caracterizar esta noción.
Childhood, street and survival: The case of La Paz and El Alto (Bolivia)
Keywords: Sociology; Childhood; Childhood; Street; Survival; Family; Work; Ngo; La Paz; El Alto; Sociología; Infancia; Infancia; Calle; Supervivencia; Familia; Trabajo; Ong; La Paz; El Alto; https://purl.org/pe-repo/ocde/ford#5.04.00